Do Psychosocial Services Make the Starting Lineup? Providing Services to Student-Athletes - Moore, Matt A (Journal of Amateur Sport, 2016)
Participation in college athletics comes with inherent risks. Many of these risks relate to the psychosocial well-being of athletes. This study examined the availability of services that treat psychosocial needs. A web-based survey was used to gather information from both athletic directors (N = 132) and athletes (N = 349). The researcher used descriptive and multivariate tests to analyze the data and found both athletic directors and athletes found psychosocial services to be less available than academic and athletic services. Additionally, NCAA division level impacted the degree of service availability. More must be done to ensure the psychosocial well-being of college athletes. This includes exploring ideas for having services more readily available.